Toxic level of iron in conilon coffee grops (Coffea canephora) in soils from the costal tablelands - KROHLING, CESAR ABEL; EUTRÓPIO, FREDERICO JACOB; FIGUEIRA, FREDERICO FIRME; CAMPOSTRINI, ELIEMAR; DOBBSS, LEONARDO BARROS; RAMOS, ALESSANDRO COUTINHO (Coffee Science - ISSN 1984-3909, 2016)
The crops conilon coffee in Espírito Santo concentrate on soils with high redox potential, in these soils predominates the Fe in reduced form and more soluble (Fe2+) which can cause interferences in development and productivity. The objective of this study was to evaluate the impacts of iron concentration in plant tissues and the productivity of crops conilon coffee (Coffea canephora) grown in soils of coastal tablelands in the State of Espírito Santo. The study was conducted in three producing properties conilon coffee located in the South of the Espírito Santo, three areas in lowland environment and three areas in the hillside environment, to compare the influence of local. We evaluated the physical and chemical composition of the soil, the concentration of nutrients in roots, stems, leaves, grains and fruit peel and productivity in two seasons. The results evidenced that the concentration of iron in all evaluated organs was higher in lowland crops and that productivity has been significantly higher in the hillside fields. We conclude that the high concentration of iron in the soil and plant organs evaluated the lowland crops may be negatively influence the productivity of crops.